Early care, education, and child development. [article]. - Philipps, Deborah A
Children growing up in the United States today typically spend a substantial portion of their early childhood years in early care and education (ECE) settings. These settings are thus an essential element of any effort to understand the ecology of early development. The frontiers of ECE research are addressing individual differences in children's responses to child care and approaching these settings both as sites for intervention research and as part of a wider web important settings in young children's lives.-(from the authors)
Keywords: Lowenstein, Amy E; Child care; Head start; Prekindergarten; Public policy; Developmental outcomes; Ecological framework